Ground Penetrating Radar Signals, An Efficient Way to Estimate Fouled Ballast - Raihan Valentino Jaya Saputra; Chiping Kuo (Himpunan Ahli Teknik Tanah Indonesia, 2023)
Mud pumping is a serious problem in railroad structures. Mud is often found in ballast structures, which can decrease the lifespan of sleepers and rail structures. Currently, the role of ground penetrating radar in investigating ballast condition is more useful than visual inspection. Ground penetrating radar can see the condition inside the ballast with the reflection of high-speed electromagnetic waves. One of the outputs from the ground penetrating radar is the graph of the signal reflection strength. Electromagnetic waves in ground penetrating radar have different reflectance strengths depending on the interfaces between different materials they pass through. For example, water-like material has a stronger signal reflection strength than gravel and soil. There are different colors used to indicate the level of signal reflection strength. Bright colors indicate a stronger level of signal reflection strength compared to dark colors. It has already been found that the dark colors of the scanning results are fouled ballast, respectively. To interpret fouled ballast conditions on the ground penetrating radar output graph, it is necessary to sort out the different colors. Therefore, this study aims to utilize design software to facilitate color selection on the ground penetrating radar output graph and determines the estimation of fouled ballast.